Torre de hanoi: uma proposta pedagógica para aprendizagem matemática e aquisição do conhecimento científico no ensino superior - Silva, Pétrick Oliveira da (Universidade Federal Rural do Semi-Árido, 2019)
Aiming to expand the knowledge about procedures that involve scientific knowledge acquisition and the process of teaching/learning, this study aims to investigate the game Tower of Hanoi as a way of studying Mathematics in the classroom. The purpose of this implementation is to show how the game may be used to proportionate better learning through an active and ludic way. Besides, the research aims to demonstrate what the role of teachers is during the process of using such a tool. To do so, field research was conducted in Higher Education because there are not many studies about it and because this study may contribute to the area. A workshop was applied to undergraduate students that major in Mathematics in a local college called Faculdade de Filosofia Dom Aureliano Matos (FAFIDAM/UECE). This bibliographic research is based on Kiya (2014) about ludic aspects as a pedagogical tool, as well as on theoretical studies from Grando (2000) about the usage of games in classrooms among others. Results suggest that the usage of mathematics games like Tower of Hanoi may significantly contribute as a teaching/learning method that enables integrated and active participation between teachers and students, thus facilitating the assimilation of theories and contents. Therefore, the study contributes to scientific knowledge acquisition
Keywords: Torre de hanói; Ensino de matemática; Aprendizagem ativa; Lúdico em sala de aula; Tower of hanoi; Mathematics teaching; Active learning; Playfulness; CIENCIAS EXATAS E DA TERRA::MATEMATICA